Assessing Income Generation from SHG Micro Enterprises: A Study of a Backward Region of Assam - Roy, Amith; Dutta, Sumanash (Indian Journal of Finance, 2012)
The paper examines the level of income generation of the SHG members from their micro enterprises and attempts to identify proximate determinants of the same. The study is based on the field survey in four Development Blocks of the Karimganj District of Assam. Both NGO connected SHGs and SHGs without having any NGO connection were taken into consideration for the better understanding of the impact of NGOs on SHGs. Regression analysis is applied in identifying factors having a significant impact on income of the SHG members. It is observed that NGO connected SHG members are the most vulnerable and are at a disadvantaged position than their counterparts so far as income from their enterprises is concerned. Education has a statistically positive impact on income so also SHG member’s savings and religion. Male female disparity is also noticeable in income from micro enterprises. Poor SHG members, who have a relative edge over others in asset possession, have also performed relatively better in generating income from their enterprises. It appears that close monitoring of the group activities and providing suitable training facility is critical to materialize the benefits of Self-help Groups. NGOs need to review their actions and have a crucial role to play in making SHG projects a success.